ALLELOPATHIC EFFECTS OF JUGLONE ON GROWTH OF CUCUMBER AND MUSKMELON SEEDLINGS WITH RESPECT TO ANTIOXIDANT ENZYME ACTIVITIES AND LIPID PEROXIDATION - Altikat, S.; Terzi, I.; Kuru, H. I.; Kocacaliskan, I. (SCIBULCOM LTD, 2013)
The effects of juglone, which exists in walnut and has allelopathic effect, on seedling growth and biochemical stress parameters were researched in this study. While a significant decrease was observed in the growth parameters (seedling elongation, fresh and dry weights) of cucumber (Cucumis sativus cv. Beith Alpha) and muskmelon (Ananas) (Cucumis melo cv. Ananas), an increase was observed in muskmelon (Kis Kavunu) (Cucumis melo cv. Kis Kavunu) by the effect of juglone. On the other hand, juglone increased malonyldialdehyde (MDA) levels of cucumber and muskmelon (Ananas) significantly, whereas it decreased MDA level of muskmelon (Kis Kavunu). However, juglone decreased catalase (CAT) and superoxide dismutase (SOD) enzyme activities of cucumber and muskmelon (Ananas), but it was contrary to those of muskmelon (Kis Kavunu). As a result of juglone effect, a positive correlation was observed between seedling growth and antioxidant enzyme (CAT, SOD) activities, but a negative correlation with lipid peroxidation (MDA) levels was seen.
Keywords: allelopathy; catalase; juglone; malonyldialdehyde; seedling growth; superoxide dismutase; ZEA-MAYS L.; OXIDATIVE STRESS; PHOTOSYNTHESIS; GERMINATION; DAMAGE; SEEDS; Environmental Sciences & Ecology